Factors Affecting Health Seeking Behavior of Elderly People in a Community of Pokhara, Nepal - Acharya, Anita; Roshan Adhikari; Bhusal, Nirmal; Acharya, Sunita (Journal of College of Medical Sciences-Nepal, 2024)
Introduction: Individuals have different opinion regarding willingness to seek help from health care services. Thus, a study aimed to find out the health care seeking behaviour, factors affecting health care seeking behaviour and association between health seeking and those factors among elderly people. Methods: Cross-sectional analytical study was conducted among 197 elderly people of 65 years and above in Pokhara Metropolitan City Ward No.28. Non probability purposive sampling technique was used. Data was collected by face to face interview technique using self-developed structured interview schedule. SPSS 16 was used for data analysis. Descriptive statistics frequency, percentage, mean and standard deviation were used for data analysis. Inferential statistics (Chi-square test) was used to reveal the association between the selected factors and health seeking behaviour.. Results: Finding showed 77.66% of respondents sought appropriate health care where as only 22.34 % of respondents sought inappropriate health care. Among those who sought care from appropriate health care, 65.48% of respondents sought care from governmental hospital. Among those who sought inappropriate health care still 22.72 % of respondents had belief in traditional healer. Accompany for the treatment of elderly was found statistically significant and other factors was not found statistically significant Conclusion: Based on the findings more than two third of the respondents reported that they seek appropriate health care. Among those respondents nearly half of respondents’ reason for seeking appropriate health care was good experience of medical treatment in the past. Among those whose health seeking behaviour is inappropriate, still one fourth of respondents had belief on traditional healer. Key words: Health seeking behavior; Elderly people; Nepal